2014
DOI: 10.4278/ajhp.130430-arb-207
|View full text |Cite
|
Sign up to set email alerts
|

School Reform: The Role of Physical Education Policy in Physical Activity of Elementary School Children in Alabama's Black Belt Region

Abstract: It appears that schools were in compliance with the state-mandated PE policies on paper but not in actuality. Students did not attend PE for 30 min/d. The implementation of PE as the sole physical activity opportunity provides inadequate amounts of physical activity during the school day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 19 publications
(25 reference statements)
1
43
0
Order By: Relevance
“…Overall, it appears that only about half of the elementary schools studied are meeting their respective DPA time requirement, as self-reported by teachers and principals. However “[the] self-reported findings may reflect what is scheduled versus actual policy implementation” (p.S75) as made evident by direct observations in a school-based PA policy evaluation in Alabama [58]. Moreover, scheduling DPA into the school day provides children with the opportunity to be active, but does not guarantee that students are active during this time.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, it appears that only about half of the elementary schools studied are meeting their respective DPA time requirement, as self-reported by teachers and principals. However “[the] self-reported findings may reflect what is scheduled versus actual policy implementation” (p.S75) as made evident by direct observations in a school-based PA policy evaluation in Alabama [58]. Moreover, scheduling DPA into the school day provides children with the opportunity to be active, but does not guarantee that students are active during this time.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was consistent with previous literature showing that PE can significantly contribute to school students PA levels. 10,12,[15][16][17]49 Students' participation in PE reduced students' non-MVPA by almost 16 and 20 min/day, increased MPA for 4 and 7 min/day and VPA for 6 and 7 min/day compared to non-PE days in U.S. and Finland, respectively. In both samples, students were more engaged in MVPAs during PE days corroborating the findings of the previous studies that have shown PE to be one of the key contributors of school day PA 12 .…”
Section: Pa During Pe and Non-pe Daysmentioning
confidence: 99%
“…In addition, research has shown that children who attend regularly PE are more physically active compared to those who attend PE less often, 13,14,15 and the binding PE requirements can increase both PA participation and intensity of PA among high school students. 13 It is noteworthy that boys have found to be more physically active during school days 16,17 compared to girls but it has been shown that these sex differences are more due to recess 17,18 and lunch break 17 PA but not PE PA. 17 Despite the evidence indicates that each additional minute of school day MVPA is associated with an additional 1.14 increase in total MVPA, 19 27 As a comparison, the U.S. score, based on high school data only, showed 41%-60 % of the U.S. schools to meet the benchmark. 28 In the U.S., Long et al 19 have shown 6-to-11-year old boys to have 36.9 minutes (5.2 min/h) of MVPA during school hours, with contributing to 46% of their total 85.9 minutes of daily MVPA.…”
mentioning
confidence: 99%
“…In the present study, the results indicated a worsening, after four weeks of PE classes alone, in the values for endurance/abdominal strength and relative fat. According to regulations, PE classes in the school environment are fundamental to improve motor activity in childhood, however, previous studies indicate that the classes offer insufficient amounts of motor activity 25,26 . In this sense, in a recent systematic review with meta-analysis 15 , researchers investigated the proportion of time spent in class devoted to moderate and vigorous physical activity.…”
Section: Discussionmentioning
confidence: 99%